Critical Physical Geography and the Study of Genocide: Lessons from Cambodia. Issue 3 (15th April 2021) - Colucci, Alex R.; Tyner, James A.; Munro‐Stasiuk, Mandy; Rice, Stian; Kimsroy, Sokvisal; Chhay, Chhunly; Coakley, Corrine
Abstract : For holistic accounts of past and present genocides to exist, the production of critical geographies of genocide, produced at the interface of human and physical geography, is vital. The emergent area of critical physical geography (CPG) scholarship stands to provide such holistic accounts in addition to providing genocide studies with a much‐needed geographic perspective, one that is grounded in the lived material realities and social relations produced by the material interactions humans have with their environments. With the land, water, and people of Democratic Kampuchea and contemporary Cambodia as subjects, this work demonstrates how a grounded, empirical CPG approach enhances our understanding of genocide and its aftermath. By examining processes of landscape transformation we suggest that violence, agriculture, and water in the context of Cambodia cannot be considered separate "social" or "natural" components of systems that are either exclusively geopolitical or physiographic. Rather, we emphasise the importance of understanding genocide and violence as internally related to the wider geomorphology—and resulting hydrology and agricultural landscape—produced under the Khmer Rouge. Our approach here has two important consequences. First, the resultant empirical knowledge serves to reinterpret how the Cambodian genocide happened, upending normative myths by demonstrating that the Khmer Rouge consistently acted with intentionality in devaluing human life to the point of mass death while transforming physical landscapes to modernise and enter the global capitalist economy. This reinterpretation serves as a framework for reinterpreting how other genocides may also be stories of continuity and acceleration, rather than aberrant rupture. Second, our CPG approach communicates to genocide studies the need to better situate genocides within their material‐geographic contexts. Specifically, that paying close attention to how humans live and die socio‐politically, relative to the changing physical landscapes around them, can yield significant insights into how and why genocides continue to happen. Abstract : In the context of the Cambodian genocide, this work demonstrates how a grounded, empirical critical physical geography approach enhances our understanding of genocide and its aftermath. By examining processes of landscape transformation we suggest that violence, agriculture, and water in the context of Cambodia cannot be considered separate "social" or "natural" components of systems that are either exclusively political or physiographic. Therefore, this work has important consequences for the value of interdisciplinary work and emphasises how genocide studies must work to better situate genocides in their historical‐geographical material contexts.